The Effect of Work Motivation, Compensation, and Work Discipline on Employee Job Satisfaction at PT Indo Muro Kencana Palangkaraya - Winokan, Aiko Melendez Ambray; Hadiyatno, Didik; Cahyaning Putri, Rahajeng (Jurnal Edueco, 2025)
The purpose of this study is to examine the influence of motivation, compensation, and work discipline on employee job satisfaction at PT Indo Muro Kencana Palangkaraya. This research uses a quantitative approach. The analytical tool used is multiple linear regression with the assistance of SmartPLS software, and the sampling technique applied is simple random sampling with a total of 70 respondents. Data were collected through observation, interviews, and questionnaires. Data processing was conducted using SmartPLS. The results of the study indicate that the motivation variable has a partial influence on employee job satisfaction at PT Indo Muro Kencana Palangkaraya. However, the compensation and work discipline variables do not have a partial influence on employee job satisfaction at the same company.